58 Optimal risk stratification pathways for patients with suspected acute coronary syndrome. (5th June 2017) - Chapman, Andrew; Anand, Atul; Sandeman, Dennis; Ferry, Amy; Shah, Anoop; Adamson, Philip; Strachan, Fiona; Gray, Alasdair; Newby, David; Mills, Nick
Abstract : Background: Novel pathways utilise low concentrations of cardiac troponin and a normal ECG to risk stratify patients with suspected acute coronary syndrome. However, clinical risk scores incorporating additional cardiovascular risk factors or physiological parameters are commonly used in practice. Whether such clinical risk scores are safer than novel pathways is uncertain. Methods: Patients with suspected acute coronary syndrome (n=1, 139) underwent high-sensitivity cardiac troponin I testing at presentation, 3 and 6 or 12 hours. We applied the HighSTEACS pathway, which rules out myocardial infarction in those without ischaemia on the ECG if troponin concentrations are <5 ng/L at presentation and symptom duration is 2 hours. Early presenters and those 5 ng/L are ruled out if absolute change is <3 ng/L at 3 hours and they remain 99th centile. We compared the HighSTEACS pathway with the HEART score (low risk 3), or a TIMI score of 0 with a normal ECG. We compared the negative predictive value (NPV) and efficacy of each approach for a primary outcome of index type 1 myocardial infarction, or type 1 myocardial infarction or cardiac death at 30 days. Results: The primary outcome occurred in 15.5% (177/1, 139). The HighSTEACS pathway ruled out 61.9% (705/1, 139) of patients by three hours, with a NPV of 99.6% [95%CI 99.1%–99.9%]. The NPV of both the HEART and the TIMI score was similar (Figure 1A), however, they identified a significantly lower proportion of patients as eligible for discharge (HEART 18% (205/1, 139), TIMI 26.3% (299/1, 139); Figure 1B ). Conclusions: The HighSTEACS pathway identifies patients at very low risk of index myocardial infarction, or myocardial infarction or cardiac death at 30 days, and rules out acute coronary syndrome in over half of patients presenting to the Emergency Department. Whilst the HEART and the TIMI scores have a comparable safety profile, they identify a significantly lower proportion of patients as low risk.